Hybrid Data Visualization Based on Depth Complexity Histogram Analysis. (5th September 2014) - Lindholm, S.; Falk, M.; Sundén, E.; Bock, A.; Ynnerman, A.; Ropinski, T.
Abstract : We present an A‐buffer based algorithm that achieves performance gains of up to eight times relative existing techniques. The algorithm contains two novel components which improve the utilization of the local cache memory on the GPU. This is particularly important for scenes with non‐uniform depth complexities and rapidly decreasing depth complexity histograms (DCHs). Abstract: In many cases, only the combination of geometric and volumetric data sets is able to describe a single phenomenon under observation when visualizing large and complex data. When semi‐transparent geometry is present, correct rendering results require sorting of transparent structures. Additional complexity is introduced as the contributions from volumetric data have to be partitioned according to the geometric objects in the scene. The A‐buffer, an enhanced framebuffer with additional per‐pixel information, has previously been introduced to deal with the complexity caused by transparent objects. In this paper, we present an optimized rendering algorithm for hybrid volume‐geometry data based on the A‐buffer concept. We propose two novel components for modern GPUs that tailor memory utilization to the depth complexity of individual pixels. The proposed components are compatible with modern A‐buffer implementations and yield performance gains of up to eight times compared to existing approaches through reduced allocation and reuse of fast cache memory. We demonstrate the applicability of our approach and its performance with several examples from molecular biology, space weather and medical visualization containing both, volumetric data and geometric structures.